Conservative Management of Extensive Iatrogenic Aortic Dissection - Tam, Derrick Y.; Mazine, Amine; Cheema, Asim N.; Yanagawa, Bobby (AORTA, 2016)
Iatrogenic aortic dissection (IAD) is a rare complication of percutaneous coronary interventions (PCI). There are no clear guidelines for IAD management, and limited data are available. Registry data and case series combined with extrapolations from our experience with spontaneous Type-A dissections suggest that very limited dissections are often managed conservatively with coronary stenting of the entry tear when possible, while more extensive dissections are managed surgically. We present a case report of a 50-year-old woman who underwent PCI for an ST-elevation myocardial infarction that resulted in an extensive IAD from the ostium of the right coronary artery to the aortic root, ascending aorta, and aortic arch. While the current evidence strongly supports surgical management of such extensive dissection, our patient was successfully managed conservatively with complete resolution according to short-term computed tomography imaging. This case suggests that conservative management may be a reasonable approach for select patients with extensive IAD.
Keywords: Iatrogenic aortic dissection; Percutaneous coronary intervention